The lack of keratinized mucosa is associated with poor peri-implant tissue health: a cross-sectional study - Kajorn Kungsadalpipob; Kakanang Supanimitkul; Sukuma Manopattanasoontorn; Navawan Sophon; Teerawut Tangsathian; Sirikarn P. Arunyanak (SpringerOpen, 2020)
Abstract Objectives The aim of this cross-sectional study is to determine the association between the absence of keratinized mucosa and peri-implant tissue health. Methods and materials This cross-sectional study comprised 412 implants from 200 patients from faculty-based clinics. Demographic, medical, and clinical information were collected. The modified sulcus bleeding index, modified plaque index, mucosal recession, probing depth, bone level, the width of keratinized mucosa, and implant status were evaluated by three calibrated examiners. Each implant was categorized into either of two peri-implant mucosa groups: keratinized mucosa (KM) or non-keratinized mucosa (NKM). The chi-square test was performed to the association between the keratinized mucosa groups and peri-implant clinical parameters and peri-implant status. Multiple logistic regression models were analyzed to test potential associations between peri-implant clinical parameters and the presence or absence of keratinized mucosa. Results Thirty-two implants (7.8%) were categorized into the NKM group. The prevalence of peri-implantitis was 12.5% and 8.3% at the subject level and implant level, respectively. The NKM group was associated with more plaque accumulation, mucosal recession, interproximal bone level ≥ 3 mm, and peri-implantitis (p < 0.05). After controlling for confounding factors, the NKM group demonstrated higher plaque accumulation, mucosal recession, and interproximal bone level ≥ 3 mm with adjusted odds ratios of 2.98 (1.33-6.66), 3.20 (95% CI, 1.03-9.90), and 4.62 (1.70-12.58), respectively. Conclusion Within the limitation of this study, the lack of keratinized mucosa around the dental implants was significantly associated with more plaque accumulation, mucosal recession, interproximal bone level ≥ 3 mm, and peri-implantitis.